2017
DOI: 10.1590/2177-6709.22.3.021-025.oin
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and orthodontic treatment: is there any direct relationship?

Abstract: Obesity is a wide-spread condition directly or indirectly connected with an increase in the prevalence of a variety of human diseases. It affects over 50% of the western overall population. In 2017, a thorough analysis of 204 studies on obesity and cancer revealed that the condition increases the risk of the following types of cancer: stomach, colon, rectal, bile duct, pancreatic, esophagus, breast, endometrial, ovarian, kidney and multiple myeloma. The first study aiming at establishing a connection between o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The impact of increased body mass index (BMI) on orthodontic tooth movement (OTM) in children and adolescents is, however, controversial showing both reduced and increased OTM rates in different studies [38][39][40][41]. Obesity exhibits a very heterogeneous clinical pattern, which could explain the different findings, since only the BMI was used for obese classification.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of increased body mass index (BMI) on orthodontic tooth movement (OTM) in children and adolescents is, however, controversial showing both reduced and increased OTM rates in different studies [38][39][40][41]. Obesity exhibits a very heterogeneous clinical pattern, which could explain the different findings, since only the BMI was used for obese classification.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity also affects systemic metabolism in bones through hormonal mechanical systems and inflammatory interactions, as well as by increasing mineral bone density. It has been demonstrated that tooth eruption speed is higher among obese individuals (Consolaro, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, as a possible result of poor diet and lack of exercise, is a growing problem in contemporary industrial societies [10]. Despite the high clinical relevance of this problem, there is not yet enough data to assess the impact of obesity on orthodontic tooth movement [11]. It is known that obesity negatively affects the entire organism due to favouring numerous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is now considered the second-most important factor after smoking for inflammation-related periodontal bone loss [16]. The most common hypothesis explains the above diseases with the increased secretion of adipokines by adipocytes [11]. Adipokines are endocrine proteins and have pro-inflammatory, but also inhibitory properties linking metabolism to the immune system [17].…”
Section: Introductionmentioning
confidence: 99%